LEGITIMASI NIKAH DARING MELALUI TAUKIL BIL KITABAH MENURUT HUKUM ISLAM DAN HUKUM POSITIF - Vijaini, Akhmad; Hasbi, Muhammad; Abda, Muhammad Syafqy; Parahdina, Soraya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This reseach is aim to know the validity and impact of teleconference-based marriage probelms in Indonesia. This research used descriptive qualitative research method and the kind of research is library research. The result of the research showed that online marriage contract has a risk and it is being a debate especially about ittihâd al-majlis, but with taukil bil kitabah as the procedure from Religious Affairs Office (KUA) which is the state official agency in marriage problem can be a solution of it. Because of the marriage through teleconference case in 1989 that became a pioneer of this marriage can be held and developed until now. Which is one of the KUA in Jakarta Selatan refuses the long distance marriage to be registered. So that the researchers felt the need to research about the validity of long distance marriage from Islamic and positive law sides. Also, so it could educate people about the risk of daring or teleconference marriage, if it occurs, it is feared that there would be a technology-based fraud such as deepfake and so forth